Level of Satisfaction of Online Learning in Mediation Lecturer Competence on Learning Motivation - Mahzura Harahap; Pristiyono Pristiyono; Junita Lubis; Muhammad Ikhlash; Agus Anjar (Budapest International Research and Critics University, 2021)
The phenomenon in the community regarding the implementation of online learning during the Covid-19 period has become a new habit for students, students, and lecturers. The sample set in this study amounted to 100 respondents (students, students, teachers, and lecturers) in the Panai Hulu sub-district. is a coastal area in Labuhanbatu Regency with a purposive sampling technique. Each indicator must be tested for instrument validity and reliability. Precise data analysis using path analysis with IBM SPSS and AMOS applications. The results of the study show that online learning has a direct effect on learning satisfaction, lecturer competence has a direct effect on learning satisfaction, and learning satisfaction has a direct effect on learning motivation. The implementation of online learning with distance learning is almost similar, the difference in online learning during the covid-19 period has used various platforms such as google classroom, google meet, zoom, Microsoft teams, and various other online learning applications, this is a manifestation of the era of the industrial revolution 4.0 in the field of learning today more real in front of us so that it has an impact on humans in the future.